2016
DOI: 10.1248/cpb.c15-00983
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Integrated Catalysts Composed of Bifunctional Thiourea and Arylboronic Acid: Asymmetric Aza-Michael Addition of α,β-Unsaturated Carboxylic Acids

Abstract: The first intermolecular asymmetric Michael addition of nitrogen-nucleophiles to α,β-unsaturated carboxylic acids was achieved through a new type of arylboronic acid equipped with chiral aminothiourea. The use of BnONH 2 as a nucleophile gives a range of enantioenriched β-(benzyloxy)amino acid derivatives in good yields and with high enantioselectivity (up to 90% yield, 97% enantiomeric excess (ee)). The obtained products are efficiently converted to optically active β-amino acid and 1,2-diamine derivatives.Ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Catalyst 3 and the monomeric counterpart catalyst 4 were synthesized according to standard procedures with more insight on the macrocycle’s role in the catalysis by comparing their catalytic activities. The corresponding isothiocyanates 7a and b were coupled with monoprotected ( R , R )-1,2-cyclohexanediamine 8 , followed by deprotection (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…Catalyst 3 and the monomeric counterpart catalyst 4 were synthesized according to standard procedures with more insight on the macrocycle’s role in the catalysis by comparing their catalytic activities. The corresponding isothiocyanates 7a and b were coupled with monoprotected ( R , R )-1,2-cyclohexanediamine 8 , followed by deprotection (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, several asymmetric reactions with aliphatic carboxylic acids using chiral organoboron and organosilane complexes have been reported [10] . Moreover, we have been involved in the asymmetric hetero‐Michael additions to α,β‐unsaturated carboxylic acids and have developed chiral thiourea–amino boronic acid hybrid catalysts and a dual catalytic system comprising an arylboronic acid and a chiral aminothiourea [11a–c] (Scheme 1‐3). In the course of these projects, mechanistic studies (kinetics, NMR titration experiments, and computational studies) revealed that high enantioselectivity was attributed to asynchronous concerted face‐selective nucleophilic addition at the β‐position and carboxylic acid‐mediated protonation at the α‐position [11d] .…”
Section: Methodsmentioning
confidence: 99%
“…The best results in term of the yield (83%) and ee (90%) were obtained while using the catalyst having a p -nitrophenyl group on the other side of thiourea moiety in CCl 4 in the presence of 4 Å molecular sieves ( Table 16 ). The yields ranged 57–89% with ee 70–97% [ 52 ].…”
Section: Reviewmentioning
confidence: 99%